2018
DOI: 10.1016/j.hpb.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy affects margins and margins affect all: perioperative and survival outcomes in resected pancreatic adenocarcinoma

Abstract: While neoadjuvant therapy is associated with decreased R1/R2-resection rates after pancreaticoduodenectomy, the poor prognostic impact of positive margins is not abrogated by neoadjuvant therapy, stressing the need for complete tumor clearance and postoperative treatment even after neoadjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…As only 2 of these studies were phase II trials 29,30 , one of which was randomized 29 all studies were therefore included in the network meta-analysis. 4 studies were prospective 3134 and 3 studies were retrospective 3537 (Supplementary Table 1a; Supplementary Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As only 2 of these studies were phase II trials 29,30 , one of which was randomized 29 all studies were therefore included in the network meta-analysis. 4 studies were prospective 3134 and 3 studies were retrospective 3537 (Supplementary Table 1a; Supplementary Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…31 did not report this outcome separately for resectable only cases but included borderline cases also in reporting the outcomes of response to NAT (complete response: 5/45; partial response: 13/45; stable disease 5/45). 6 studies (n = 17596) reported the number of patients in the SFadj pathway who received adjuvant therapy 3133,3537 giving a pooled proportion of 63.01% (95% CI: 59.452–66.489).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, clinicians should consider more aggressive postoperative treatments or neoadjuvant therapy first, rather than upfront surgery in these cases. Neoadjuvant chemoradiation, which has the advantage of increased R0 rates, is widely performed recently when it is deemed difficult to obtain sufficient surgical margin [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 and de Geus et al . 37 used the same NCD database and data collected during overlapping periods from 2006 to 2012. Furthermore, two other studies by Roland et al .…”
Section: Discussionmentioning
confidence: 99%